Traditional Law vs. Islamic Law; An Analysis of Muslim Community Awareness in Inheritance Issues - Fahmi Fatwa Rosyadi Satria Hamdani; Suci Pebrianti; Liza Dzulhijjah; Hudzaifah Muhammad Maricar (Al-Ahkam, 2022)
The system of inheritance distribution in Islamic law, normatively, between men and women is 2:1. Meanwhile, the traditional inheritance system of the Cipicung Girang community, Cidadap District, Bandung City, where the majority of the population is Muslim, has divided men and women equally, namely 1:1. Another uniqueness of the system is that the house they live in belongs to the child who is the last to take care of his parents. The problem is, the customary inheritance system is used by the majority Muslim population. This study aims to analyze the factors that influence public awareness in the distribution of inheritance. This study uses a mix-method with interactive analysis techniques and assisted by Smart PLS software to test the relationship between variables. This study found that inheritance follows the local traditional system because girls take care of their parents, while men are busy working. Another finding is that literacy factors have a greater influence on people's awareness and loyalty compared to religiosity and perceptions of inheritance.